University proceedings. Volga region. Natural sciences - G.S. Rozenberg; N.V. Kostina; G.E. Kudinova; A.G. Rozenberg (Известия высших учебных заведений. Поволжский регион: Естественные науки)
Background. Clean fresh water is a renewable resource, the value of which is constantly increasing. The possibility of cooperation between the BRICS countries in solving water and environmental problems of the great river basins – the Amazon, Volga, Ganges, Yangtze and Orange – is considered. Materials and methods. They are compared by a number of geographical parameters (length, basin area, volume of water resources, etc.). It is shown that these rivers are similar to varying degrees in many parameters of anthropogenic impact (pollution, regulation, uncontrolled use, urbanization, etc.). The BRICS countries exceed the G7 countries in fresh water reserves by more than 2.3 times; In terms of fresh water consumption per capita, the G7 countries are 10 times higher than the BRICS countries. Results and conclusions. Using the Volga and Yangtze as examples, a methodology for comparing the socio-ecological-economic systems of the basins is proposed.